Antimicrobial susceptibility of Moraxella bovis determined by agar disk diffusion and broth microdilution. - Webber, J J (1982)
The antimicrobial susceptibility of 84 isolates of Moraxella bovis was evaluated by the standard agar disk diffusion and broth microdilution procedures. All isolates were resistant to cloxacillin by disk diffusion, with 97% of isolates having a minimal inhibitory concentration of greater than or equal to 2 micrograms/ml. Of the hemolytic isolates, 68% were resistant to streptomycin. A high frequency of susceptibility was recorded for all other antimicrobial agents tested. Quantitative data supported the use of sulfonamides, but not tylosin, for parenteral infectious bovine keratoconjunctivitis therapy.